The functional divergence of biomass partitioning, carbon gain and water use in Coffea canephora in response to the water supply: Implications for breeding aimed at improving drought tolerance - Silva, Paulo E. M.; Cavatte, Paulo C.; Morais, Leandro E.; Medina, Eduardo F.; DaMatta, Fábio M. (Environmental and Experimental, 2012)
Robusta coffee (Coffea canephora) is widely cultivated in regions where water availability is the major environmental constraint affecting crop production. The functional divergence associated with biomass partitioning, carbon gain and water use in response to water supply was examined in 10 one-year-old clones of robusta coffee with varying degrees of droughttolerance. The plants were grown outdoors in 24 L pots and either irrigated or subjected to a four-month water deficit. Under conditions of ample irrigation, clones with superior water use ability (i.e., a higher water potential,transpiration rate, apparent hydraulic conductance and biomass partitioning into roots and a lower wood density) displayed enhanced carbon gains. In contrast, under drought conditions, clones that postponed dehydration via more conservative water use rates showed lower relative decreases in stomatal conductance, photosynthetic rates and biomass accumulation. Isotopic signatures (13C) might be useful for identifying clones with improved performance under drought conditions. Our results suggest that combining useful morphological and physiological traits facilitates the successful assessment of coffee clonal performance in response to drought at the seedling stage. This strategy may be valuable when exploring a large number of genotypes in coffee-breeding programs because it reduces the time and resource costs that would otherwise be wasted on potentially undesirable genotypes.
Keywords: Breeding; Coffee; Drought tolerance; Photosynthesis; Water deficit